Depression and anxiety during the mandatory isolation period due to COVID-19 in Lima Metropolitan Area - Prieto Molinari, Diego E. (2020)
Background: the implementation of public health measures such as quarantines and isolation is a useful strategy for disease control; nonetheless, said measures may also have consequences on mental health. Objectives: to describe the prevalence of depression and anxiety symptoms in adults living in Lima Metropolitan Area during the social isolation period due to the COVID-19 pandemic. Method: items from the Lima Anxiety Scale [EAL-20] and the Depressive Psychopathology Scale [EPD-6] were used in a sample of 565 adults living in Lima Metropolitan Area during the health emergency. Results: prevalence of anxiety and depression symptoms were identified. Also, differences regarding sex, age, education level, and modality of work or study were found. Conclusions: the mandatory isolation period involves the prevalence of anxiety and depression symptoms in adults living in Lima Metropolitan Area. Such phenomena might occur in different ways according to the different sociodemographic variables. These findings are consistent with those from international studies; thus, they should be considered when making decisions related to public health policies. Authorship contribution DEPM: Contribution in the conception and design of the article, bibliographic review, writing and revision critique of the results to generate discussion of equitable manner. GLAB: Contribution in the conception and design of the article, bibliographic review, writing and revision critique of the results to generate discussion of equitable manner. IDP: Contribution in the conception and design of the article, bibliographic review, writing and revision critique of the results to generate discussion of equitable manner. GLVB: Contribution in the conception and design of the article, bibliographic review, writing and revision critique of the results to generate discussion of equitable manner. LAMS: Contribution in the conception and design of the article, bibliographic review, writing and revision critique of the results to generate discussion of equitable manner. CSLN: Contribution in the conception and design of the article, bibliographic review, writing and revision critique of the results to generate discussion of equitable manner. KAUB: Contribution in the conception and design of the article, bibliographic review, writing and revision critique of the results to generate discussion of equitable manner. ACHZ: Method development and analysis statistical data.